DEVELOPMENT OF PLANET EDUCATION (PLANETION) LEARNING MEDIA BASED ON ADOBE FLASH CS6 IN CLASS VI SCIENCE LEARNING PRIMARY SCHOOL - Nurillah Manahim, Bisma; Kuswandi, Iwan; Zainuddin, Zainuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is to create a product in the form of interactive planetary learning media based on Adobe Flash CS6 on the characteristics of planets in the solar system as a valid, practical and effective learning media for class VI. The aim of this research is to determine the process and effectiveness of using the planetion interactive learning media development product. The method used is R&D (Research and Development) and the development model uses the ADDIE model. Material validation obtained a score of 97% and media validation obtained a score of 88%. Practicality data obtained from the teacher response questionnaire obtained a score of 97% and the student response questionnaire obtained a score of 92%. Effectiveness data obtained from the results of students' posttest questions received a score of 90. So it can be concluded that the development of planetion media based on Adobe Flash CS 6 software, material on the characteristics of planets in the solar system for class VI students is very suitable for use in the learning process.